Variação na dieta da tartaruga verde, Chelonia mydas, e o impacto da ingestão de lixo ao longo da costa brasileira - Santos, Robson Guimarães dos (2014)
We studied the diet of green turtle, Chelonia mydas, and the factors involved in diet variation. We also evaluated the impact of debris ingestion and thefactors that may explain debris ingestionby many marine animals. In the diet study, we evaluated more than 400 turtles, including original data and data from the literature, distributed in a latitudinal gradient and different environments. Turtles fed mainly on algae, however,they showed a high foraging plasticity, regarding both foraging strategy and diet items. In cold waters with low algae availability, turtles shifted from an herbivore diet to a more carnivore one. This diet shift also resulted in a change in the foraging strategy, in which, turtles shifted from a benthic foraging to a pelagic foraging. This foraging strategy shift was also found in turtles from the estuarine areas. The green turtle foraging plasticity was due to intrinsic (physiological restrains) and extrinsic (regional and local) factors. Differences in foraging strategy also mean differences in exposure to threats, such as debris ingestion, which was higher in animals that exhibit a pelagic foraging strategy, despite being a widespread phenomenon (70.6%; N = 265). Plastic was the most ingested material, and it comes mainly from food related items and plastic bags. Our study also showed that a very small amount of debris (0.5 g) is sufficient to kill a turtle. This result indicated that the mortality potential of debris ingestion is much higher than the observed mortality. The real threat imposed bydebris ingestion is masked by the high mortality caused by fishery, because the former derived from a chronicle process. A common hypothesis to explain debris ingestion is that debris resembles a typical prey item (e.g. jellyfish and plastic bags). However, we showed that the debris ingestion involves broader reasons, and we used green turtles, seabirds and fishes to show the importance of other factors, such as: debris availability, foraging strategy, debris detectability and diet amplitude. We believe that the ingestion of debris occurs due to a broad evolutionary trap, and may affect much more species than it has been reported. Disarming this trap will be particularly difficult due to continuous and intense release of plastics in the ocean and their high persistence in the environment.